Production of enhanced stability colloidal system for thermal application / Mohd Nashrul bin Mohd Zubir - Mohd Zubir, Mohd Nashrul (2015)
It is evident that studies on colloidal stability have been a major subject of interest among researchers both in academia and industry. Thus the present research was directed towards understanding mechanisms that govern colloidal stability, exploring viable, scalable and environmentally ‗greener‘ techniques to improve the stability based on existing and innovative approaches and ultimately paving routes for applying the concept into real engineering applications. Three major topics were pursued within the current research perspective. The first topic emphasized on the exploration of surfactant free stabilization technique to improve the stability of aggregated prone structure in colloidal system. To achieve this objective several unconventional routes have been adopted based on different strategies. The first approach involved incorporation of highly charged nanoparticles which interact with the weakly charged aggregated colloidal systems to prolong and enhance their overall stability. Series of experimental results strongly suggested the improvement of weakly charged colloidal stability in the studied bimodal system. The subsequent part of the research concerned with the use of Graphene Oxide (GO) nanosheets as a new class of stabilizer for different carbon allotropes. Two additional carbonous materials under the family of fullerene (Carbon Nanofibers- CNFs) and graphite (Graphene Nanoplatelets - GnPs) were introduced within the present study on top of the commonly investigated GO-Carbon Nanotubes (CNT) hybrid. The results elucidated the ability of GO to segregate the above carbon allotropes to yield much dispersed colloidal suspension. Further, investigation was conducted on the use of GO to improve the solubility of weakly charged GnP. The results showed that GO was capable of stabilizing GnP colloid near its isoelectric point to prevent rapid agglomeration and sedimentation. The research continued with the use of plant based phytochemical extract on the dissolution of carbon nanotubes (CNTs) bundles in aqueous based solution. The results led to the fact that type, concentration and molecular structure of phytochemicals affect the level of CNT stability. Improvement in thermal conductivity measurements along with negligible increase in viscosity were recorded by using the above approach. The second topic focused on the benign and facile preparation of highly stable Reduced Graphene Oxide (RGO) and its role on enhancing the thermophysical properties of heat transfer liquid. GO was prepared and subsequently reduced by using Tannic Acid which served as natural based environmentally benign reducing agent. Further, a meticulous amount of different high purity carbon sources (i.e., Carbon Nanotube-CNT, Carbon Nanofiber-CNF and Graphene Nanoplatelets-GnP) were introduced to the RGO sheets to form series of hybrid complexes. The results obtained showed that GO was successfully reduced based on the material characterization evidences. Moreover, the addition of highly conjugated carbon structures on RGO has proven to promote highly efficient thermal transport with minimal penalty on viscosity increment. The final topic dealt with the field testing of various colloidal mixtures with improved stability within energy transport system. This topic was divided into three specific studies. The first study involved the use of RGO and its hybrid complexes to improve the convective heat transfer performance in close conduit configuration. A close loop pipe flow experimental set-up working in turbulent mode and subjected to constant heat flux was established. It was discovered that the results obtained closely coincide to the previous documented findings on heat transfer enhancement related to the addition of graphene based materials. Studies on hydrodynamic parameters indicated negligible increase in pressure loss as well as friction factor for RGO and its hybrid mixtures. The second study highlighted on the numerical study on the effect of implementing temperature dependent thermopysical properties, constant mean velocity as well as fully developed inlet boundary condition for velocity and turbulent parameters in heat transfer performance of nanofluid closed conduit turbulent flow. The investigation was conducted in a 2-D pipe flow model. TiO2 based nanofluid was selected as colloidal medium within the present study. Series of results confirmed the effectiveness of incorporating the above features on gaining much realistic representation of heat transfer behavior. The final part of the topic involved a comparative assessment between experimental and numerical approaches on convective heat transfer in close conduit by using RGO-based colloid. A computational domain resembling the previously constructed experimental test section was established. The results showed that the surface temperature along the axial parameter of the pipe remained relatively close between the two approaches. Further, the numerical heat transfer property was found to move closer toward experimental results at the downstream section of the conduit, suggesting the ability of single phase simulation strategy to capture the nature of heat transfer within the thermally and hydrodynamically developed regions. Friction factor calculation from numerical data revealed close resemblance to experimental results.